Penerapan Pelaksanaan Kegiatan Pendukung Bimbingan Dan Konseling Di Sekolah - Rahmi Fratiwi; Yarmis Syukur; Dina Sukma (CV. ITTC INDONESIA, 2025)
Guidance and Counseling (BK) is an important service in the world of education which aims to help students develop their potential, overcome problems and improve the quality of their personal, social, learning and career lives. In order for this goal to be achieved optimally, various supporting activities are needed which are preventive, curative and developmental in nature. This research aims to analyze the implementation of guidance and counseling (BK) support activities in schools as part of efforts to improve the quality of services to students. The method used is literature study, by analyzing various relevant sources, such as journals, books and previous research reports related to the implementation of BK. The population in this study includes secondary level formal education institutions in Indonesia, with a focus on schools that have implemented the BK program. The research results show that the success of the BK program is greatly influenced by the availability of facilities, the competence of teaching staff, and support from the school. However, the main challenge found was the lack of special time allocation and lack of understanding by some parties regarding the importance of guidance and counseling in the school environment. This research emphasizes the importance of implementing guidance and counseling support activities that are integrated with the learning system to create an educational environment that is student-centered and supports student development academically, emotionally and socially.